O reino e as rebeldes: funcionamento discursivo do destacamento em capas de revista semanais de informação - Cabral, Luís Rodolfo (2021)
The objective of this research is to investigate the discursive functioning of weekly information magazine covers, verifying the role of the detached utterances in this discursive genre. This researched started started from an empirical observation that magazine covers can either circulate independently as a production from a full edition, or it can be made up of utterances previously produced from other texts. For the research, it has been created a collection of editions of the four weekly information magazines circulating in Brazil - Carta Capital, Época, Isto É and Veja - published between January 2015 and September 2016, a period corresponding to the second term of President Dilma Rousseff. In order to define the conditions for enunciating these productions, works from the Political Science area were convenient. The corpus was delimited progressively as the research progressed. Supported by the French Discourse Analysis, specifically by concepts postulated by Maingueneau, this research takes two theoretical and methodological principles: the primacy of interdiscourse, and the scenes of enunciation. There are two units of analysis for this research: a topic unit, the gender, which allows the treatment of the corpus regarding the conditions of felicity and the potential for irradiation; and a no-topic unit, parcours, which contemplates the phenomenon of detachment, approached from the perspective of aphorizing enunciation, distinguishing aphorizations, particiations, and interpretative frameworks for these phrases without text. The analysis of the corpus allows us to make the following considerations: the magazine covers studies are composed by three different zones, each which of them the verbal and non-verbal utterances are placed to. Theses utterances come from two different irradiation process, as a result from an agency of a complex enunciative instance, which supports the role of detachment in this genre. The discursive functioning of the utterances in the magazine covers suggests that they were produced under the aphorizing regime, and that the complex enunciative instance, in this genre, assumes the role of aphoriser, the one to whom the enunciative responsibility for an aphorization is attributed. Since, from the classificatory point of view, magazine covers cannot be placed into the categories of primary aphorisations nor of secondary aphorisations, we strongly suggest the term “iconophorization” for cases liked the one studied in this research in which the iconotext is strictly the result of an aphorizing detachment of the two materialities - verbal and non-verbal